Recent Advances and the Interpretation of Geological Structure of New Brunswick - Rast, N.; Stringer, P. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary The paper reviews the Precambrian and Paleozoic stratigraphy and structure of New Brunswick against the background of the theory of plate tectonics. The major subdivisions of the Appalachian-Caledonian orogenic belt are examined and a conclusion is reached that as a result of successive Penobscot, Taconic and Acadian orogenic disturbances parts of Paleoamerica and Paleoeurope are so sutured that the formerly intervening oceanic crust has either been entirely obducted onto the continents or subducted below them. The evolution of the orogenic belt in New Brunswick and adjacent regions can be explained with reference to the formation of successive volcanic arcs.